Pengaruh Live Streaming terhadap Keputusan Pembelian Produk Fashion di Shopee melalui Minat Beli sebagai Variabel Intervening (Studi Kasus pada Gen Z di Kabupaten Jember) - Nadhifah Efendi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This research is motivated by the increasing use of live streaming features on e-commerce platforms as a digital marketing strategy that can influence consumer behavior, particularly among Generation Z, when purchasing fashion products. This study aims to analyze the influence of live streaming on fashion product purchasing decisions through purchase intention as an intervening variable among Generation Z Shopee app users in Jember Regency. This study used a quantitative approach with a survey method. Data were collected by distributing questionnaires to 141 respondents selected using a purposive sampling technique in accordance with the research criteria. Data analysis was performed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) using SmartPLS software to test validity, reliability, and the direct and indirect effects between variables. The results show that live streaming has a positive and significant effect on purchase intention. Purchase intention also has a positive and significant effect on purchase decisions. Furthermore, live streaming has a positive and significant effect on purchase decisions through purchase intention as an intervening variable, indicating a strong mediating role. The coefficient of determination and predictive relevance values indicate that the research model has excellent ability to explain endogenous variables. The conclusion of this study indicates that the more effective the live streaming implementation, the higher the purchasing interest and purchasing decisions for fashion products among Generation Z in Jember Regency.
Approved by Teddy
Keywords: Live Streaming; Minat Beli; Keputusan Pembelian